Study of incidence of urinary tract infection during pregnancy and its effect on maternal and perinatal outcome - Mahor, Suman; Malviya, Ritika; Goyal, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Urinary tract infection is the commonest bacterial infection in pregnancy, especially in developing countries like India. It has several adverse outcomes not only in the mother but also in the fetus. This study aims to determine the incidence of UTI during pregnancy, the commonest micro-organism causing UTI, and to find out the impact of such infection on maternal and fetal outcomes. Methods: This observational study was carried out in the department of obstetrics and gynaecology Deen Dayal Upadhyay Hospital, New Delhi over a period of 10 months. A total of 196 pregnant women attending the outdoor hospital for ANC check-up without any medical disorder or previous adverse pregnancy outcomes were included in this study. Urine routine microscopy was done as a screening test for UTI. They were followed through their pregnancy and puerperium due to any pregnancy complication and perinatal outcome. Results: Incidence of urinary tract infection was 12.2%, of which 8.2% were asymptomatic and 4.08% were symptomatic. It was found that the incidence of UTI was highest in the age group of 18 to 25 years and also found that UTI was more common in the second (16.7%) and third (16.7%) trimester and lowest in the first trimester (5.7%). Women who had anaemia, pregnancy-induced hypertension, preterm labour, chorioamnionitis, perinatal mortality, and puerperal pyrexia had a high incidence of UTI than those who had not. Conclusions: From this study, we concluded that screening for UTI should be a part of routine antenatal care, and also there is a need to initiate an awareness program to educate women about UTI and their adverse fetomaternal outcome so that prompt and effective treatment can be done.